Enzyme Promiscuity in Serotonin Biosynthesis, From Bacteria to Plants and Humans - Gonçalves, Sara; Nunes-Costa, Daniela; Cardoso, Sandra Morais; Empadinhas, Nuno; Marugg, John David (Frontiers in Microbiology, 2022)
Serotonin is a phylogenetically ancient compound found in animals, plants, and some bacteria. In eukaryotes, serotonin is synthesized from the aromatic amino acid tryptophan via the key enzymes Aromatic Amino Acid Hydroxylase (AAAH) and Aromatic Amino Acid Decarboxylase (AAAD). Serotonin is also an intermediate in the melatonin biosynthetic pathway and is involved in several vital functions. In humans, serotonin is produced in the gut and in the brain, is critical in the regulation of multiple body functions, and its depletion has been implicated in multiple neurological disorders including depression and Alzheimer’s Disease, as well as other peripheral conditions namely irritable bowel syndrome and fibromyalgia. The serotonin biosynthetic pathway is well described in eukaryotes, but very little is known about this pathway in bacteria. Evidence points to similar pathways since eukaryote-like AAAH and AAAD (and their genes) have been identified in multiple bacteria, even though serotonin production has not yet been detected in most species. Although data on bacterial tryptophan decarboxylase genes are very limited and no bacterial tryptophan hydroxylase genes have been identified to date, evidence suggests that serotonin production in bacteria might occur through different AAAH and AAAD. Substrate promiscuity in these enzymes has been previously reported and seems to be the key aspect in bacterial serotonin synthesis. Considering the human gut microbiota as a potential source of serotonin, further investigation on its biosynthetic pathways in microbes might lead to important discoveries, which may ultimately foster the development of new therapeutic strategies to treat serotonin depletion-related disorders in humans.